1998
DOI: 10.1891/0886-6708.13.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Violence, Self-Control, and Conjugal Violence: A Comparative Analysis of Physical Violence and Psychological Aggression

Abstract: This paper is a sequel to Avakame (1998), a study which sought to determine whether (a) violence in families of origin affects males’ psychological aggression toward wives, and (b) whether the intergenerational transmission effect is solely direct or mediated by Gottfredson and Hirschi’s concept of self-control. The current research extends these questions to females’ psychological aggression as well as males’ and females’ physical violence. The models were estimated using data from the 1975 National Family Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 0 publications
4
44
0
2
Order By: Relevance
“…Some scholars propose that applications of social learning theory to interpersonal violence have been excessively simplistic (Avakame, 1998;Widom, 1989). Although we contend that we are not testing a complete model of social learning theory, we are examining one component of it-the relationship between childhood abuse and adult violence.…”
Section: Self-control Theorymentioning
confidence: 96%
“…Some scholars propose that applications of social learning theory to interpersonal violence have been excessively simplistic (Avakame, 1998;Widom, 1989). Although we contend that we are not testing a complete model of social learning theory, we are examining one component of it-the relationship between childhood abuse and adult violence.…”
Section: Self-control Theorymentioning
confidence: 96%
“…Important research by Avakame (1998) suggests that a link exists between low self-control and physical and psychological intimate partner violence for both men and women. Furthermore, Avakame (1998) suggests that physical punishment during childhood by mothers predicts low self-control among females.…”
Section: Intergenerational Transmission Of Violence and Stalking Victmentioning
confidence: 99%
“…Important research by Avakame (1998) suggests that a link exists between low self-control and physical and psychological intimate partner violence for both men and women. Furthermore, Avakame (1998) suggests that physical punishment during childhood by mothers predicts low self-control among females. Given these findings and the close relationship between intimate partner violence and stalking (Logan et al 2000), there is substantial evidence to suggest that stalking victimization may also be related to childhood maltreatment.…”
Section: Intergenerational Transmission Of Violence and Stalking Victmentioning
confidence: 99%
“…In other words, the reason that peer associations appear to be related to crime is that criminals are more likely to fraternize with persons like themselves. Others, however, have suggested that social learning processes, particularly those learned from association with delinquent peers, mediate the effects of selfcontrol (Avakame, 1998;Gibson & Wright, 2001;Winfree & Bernat, 1998). For example, Gibson and Wright (2001) found that the interaction between self-control and delinquent peers is potentially the most fruitful indicator of criminal involvement (also see Wood, Cochran, Pfefferbaum, & Arneklev, 1995).…”
mentioning
confidence: 99%